Understanding Empowerment in Social Media Context: Lessons from Indonesian Migrant Domestic Workers. (2018) - Wijaya, Stevanus Wisnu; Watson, Jason; Bruce, Christine
This paper presents the shared practices amongst Indonesian migrant users of an online community hosted in Facebook which potentially empower them. We conducted a virtual ethnography study which was comprised of online observations and interviews. The results show that shared practices within the online community empower migrants by enhancing their psychological wellbeing, and increasing awareness of migrants' rights. In addition, online shared practices empower a migrant community by facilitating them to organise collective actions. In general, two types of empowerment were observed by this study: individual and community. Empowerment was seen as shared practices amongst individual members of the online community which enhance capability to cope with social challenges and allow them to achieve better wellbeing. Further, empowerment was observed at the community level where the combined assets of individuals was found to increase the capacity of the community as a whole, allowing control over common factors and decisions that influence their capabilities to take actions towards changes.